Aplikasi Model Problem Based Learning Sebagai Motivasi Dalam Pembelajaran Fiqih - Sufinatin Aisida (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2017)
The skills of a teacher are not only able to provide maximum service in physical terms but more than that, the teacher should be able to encourage his students to be motivated to follow the learning process and actively involved in the process therein. Therefore the selection of learning model is very determinant of success in the learning process, one of the learning model is model Problem Based learning, this model is considered quite significant in its application on the subjects of fiqih because the subjects of fiqih is a subject of worship and muamalah directly students in touch With the reality of everyday life and interact with the surrounding environment. In This Paper We describe the stages in the basic learning model better. There are six stages in the PBL model that can be applied in the subjects of fiqih. They are finding a problem, building a work structure, establishing problems, gathering and sharing information, formulating solutions, presenting solutions when the Post learning. The function of teachers in this learning model is as a facilitator